2023
DOI: 10.1101/2023.09.15.557808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Driver lines for studying associative learning in Drosophila

Yichun Shuai,
Megan Sammons,
Gabriella R Sterne
et al.

Abstract: The mushroom body (MB) is the center for associative learning in insects. In Drosophila, intersectional split-GAL4 drivers and electron microscopy (EM) connectomes have laid the foundation for precise interrogation of the MB neural circuits. However, many cell types upstream and downstream of the MB remained to be investigated due to lack of driver lines. Here we describe a new collection of over 800 split-GAL4 and split-LexA drivers that cover approximately 300 cell types, including sugar sensory neurons, put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 146 publications
0
4
0
Order By: Relevance
“…Alternatively, different subsets of Gr64f-Gal4 -expressing neurons may promote opposing behaviors, as suggested by a recent study, 46 and high levels of activation may preferentially recruit aversive circuits. While it is possible that aversive Gr64f-Gal4 -expressing neurons represent off-target cells that do not endogenously express Gr64f, flies naturally avoid sugar in some contexts, such as egg-laying, and subsets of sugar-sensing neurons have been shown to elicit aversion.…”
Section: Discussionmentioning
confidence: 92%
“…Alternatively, different subsets of Gr64f-Gal4 -expressing neurons may promote opposing behaviors, as suggested by a recent study, 46 and high levels of activation may preferentially recruit aversive circuits. While it is possible that aversive Gr64f-Gal4 -expressing neurons represent off-target cells that do not endogenously express Gr64f, flies naturally avoid sugar in some contexts, such as egg-laying, and subsets of sugar-sensing neurons have been shown to elicit aversion.…”
Section: Discussionmentioning
confidence: 92%
“…Lines whose names are shown in black font were described in Aso et al, 2014a . Lines from other studies are shown brown font and their sources were as follows: SS01308, Aso et al, 2019 ; G0239, Chiang et al, 2011 ; SS46348, Otto et al, 2020 ; MB618B, SS01127, SS01188, SS01194, SS01298, SS01337, and SS01388, Shuai et al, 2023 release: https://splitgal4.janelia.org . …”
Section: Resultsmentioning
confidence: 99%
“…We therefore first focused on γ KC‐to‐MBON‐γ1pedc synaptic transmission. To selectively study these synapses, we expressed red‐shifted channelrhodopsin, CsChrimson (Klapoetke et al., 2014), in a small subset of γ KCs using γ KC‐specific split‐GAL4 driver MB623C (Shuai et al., 2023) together with a stochastic expression system SPARC (Isaacman‐Beck et al., 2020). By using the ‘S’ (or sparse) variant of the SPARC system, we can reliably label a random ∼3%–7% of γ KCs (Isaacman‐Beck et al., 2020), roughly equivalent to the fraction of KCs reliably responsive to a typical odour (Honegger et al., 2011).…”
Section: Resultsmentioning
confidence: 99%